2016
DOI: 10.1101/gad.288415.116
|View full text |Cite
|
Sign up to set email alerts
|

Control of inflorescence architecture in tomato by BTB/POZ transcriptional regulators

Abstract: Plant productivity depends on inflorescences, flower-bearing shoots that originate from the stem cell populations of shoot meristems. Inflorescence architecture determines flower production, which can vary dramatically both between and within species. In tomato plants, formation of multiflowered inflorescences depends on a precisely timed process of meristem maturation mediated by the transcription factor gene TERMINATING FLOWER (TMF), but the underlying mechanism is unknown. We show that TMF protein acts toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
102
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 61 publications
5
102
0
Order By: Relevance
“…Although BOP-like genes do not function as transcription factors, they have been shown to interact with them in Arabidopsis (25) as well as tomato. For example, the nuclear transport of tomato BTB/POZ genes is mediated by their interaction with transcription factors such as TERMINATING FLOWER (46), indicating that tru1 may be part of a transcriptional complex. Thus, the complex developmental changes conditioned by bop1 mutants in different species may be due to misexpression of multiple downstream target genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although BOP-like genes do not function as transcription factors, they have been shown to interact with them in Arabidopsis (25) as well as tomato. For example, the nuclear transport of tomato BTB/POZ genes is mediated by their interaction with transcription factors such as TERMINATING FLOWER (46), indicating that tru1 may be part of a transcriptional complex. Thus, the complex developmental changes conditioned by bop1 mutants in different species may be due to misexpression of multiple downstream target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the BTB/POZ clade of ankyrin repeat proteins have a wide range of functions (25) including establishment of floral and inflorescence meristem determinacy (45)(46)(47), but those most similar to tru1 appear to have a clear function in specifying leaf cell identities. The founding members of this clade, BLADE ON PETIOLE 1 and 2, display ectopic distal blade tissue growing down the petiole and lack of stipules (24,48).…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, AtCUC1 promotes the expression of LIGHT‐DEPENDENT SHORT HYPOCOTYLS 3 ( AtLSH3 ) and its paralog AtLSH4 , which are members of the Arabidopsis LSH1 and Oryza G1 gene family ( ALOG ; Cho and Zambryski, ; Takeda et al ., ). Furthermore, in Lycopersicon esculentum it has been shown that ALOG proteins are able to interact with NBCL proteins (Xu et al ., ). Thus, in L. japonicus , boundary zone patterning and regulation might be carried out through a similar CUC/ALOG/NBCL module in which LjNBCL1 plays a major role.…”
Section: Discussionmentioning
confidence: 97%
“…In Arabidopsis, AtBPMs were expressed at a significantly higher level in floral buds and open flowers, and BPM-silenced plants exhibited altered flower development [17]. In tomato, SlBOPs (Solanum lycopersicum BLADE-ON-PETIOLE), which are BTB transcriptional regulators, can interact with the transcription factor TERMINATING FLOWER (TMF) to control inflorescence architecture [50]. This suggests that BTB-containing proteins may participate in flower development processes.…”
Section: Discussionmentioning
confidence: 99%